Cirkennedya porlockensis, a new genus and species of digenean from the sunfish Mola mola (L.) - Gibson, D. I.; Bray, R. A. (Journal of Helminthology, 1979)
Cirkennedya porlockensis gen. et sp. nov. is described from the intestine of Mola mola off Porlock, Somerset, England. The Systematic position of this new genus is discussed. It appears to be the first example of the family Macroderoididae to be reported from a marine teleost host. The status of this family in relation to the Plagiorchiidae is briefly commented upon.